Ability of device to collect bacteria from cough aerosols generated by adults with cystic fibrosis - Ku, David N. (F1000Res, 2016)
Background: Identifying lung pathogens and acute spikes in lung counts remain a challenge in the treatment of patients with cystic fibrosis (CF). Bacteria from the deep lung may be sampled from aerosols produced during coughing. Methods: A new device was used to collect and measure bacteria levels from cough aerosols of patients with CF. Sputum and oral specimens were also collected and measured for comparison. Pseudomonas aeruginosa, Staphylococcus aureus, Klebsiella pneumoniae, and Streptococcus mitis were detected in specimens using Real-Time Polymerase Chain Reaction (RT-PCR) molecular assays. Results: Twenty adult patients with CF and 10 healthy controls participated. CF related bacteria (CFRB) were detected in 13/20 (65%) cough specimens versus 15/15 (100%) sputum specimens. Commensal S. mitis was present in 0/17 (0%, p=0.0002) cough specimens and 13/14 (93%) sputum samples. In normal controls, no bacteria were collected in cough specimens but 4/10 (40%) oral specimens were positive for CFRB. Conclusions: Non-invasive cough aerosol collection may detect lower respiratory pathogens in CF patients, with similar specificity and sensitivity to rates detected by BAL, without contamination by oral CFRB or commensal bacteria.